EXPLORATORY FACTOR ANALYSIS OF MORAL IDENTITY OF NURSING STUDENTS, BOROMARAJONANI COLLEGE OF NURSING, BANGKOK - Thammaraksa, Pimrat; Sirisupluxana, Piriyalux; Boonvas, Kwanta; Kosolchuenvijit, Jindamas (JOURNAL OF THE POLICE NURSES AND HEALTH SCIENCE, 2022)
This survey research aimed to explore components of nursing students’ moral identity. The sample included five hundred seventy-five nursing students, from the 1st year to the 4th year, at Boromarajonani College of Nursing. Data were collected by using a nursing students’ moral identity questionnaire and it was proofed for the content validity. The content validity index (CVI) was .88. The Cronbach’s alpha coefficient was .91. Data were then analyzed by descriptive statistics and exploratory factor analysis (EFA). The results revealed 9 components of nursing students’ moral identity, including 1) eco-college, 2) sufficiency economy philosophy, 3) new technology and innovation, 4) bonding, 5) honesty, 6) code of conduct, 7) service mind, 8) analytical thinking and 9) participation. All components could explain 57.214% of nursing students’ moral identity. Focusing on each component, it was found that each component could explain the total variances of the nursing students’ moral identity, which were 22.218, 7.882, 5.167, 4.703, 4.059, 3.770, 3.345, 3.161 and 2.908, respectively. This finding suggested that nursing students’ moral identity components can be used to formulate policies, evaluations, and guidelines for promoting the moral identity of nursing students in order to accomplish desirable nursing graduates.